OPTIMALISASI PENGGUNAAN DANA KEISTIMEWAAN DIY DALAM KESENIAN KARAWITAN DAN GEJOG LESUNG KAMPUNG TEGAL KENONGO - Hawawi, Alfina (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
This study aims to analyze the optimization of the use of special funds in the karawitan and gejog lesung arts of the Tegal Kenongo Village community. This study uses a qualitative method that examines the use and results of the distribution of special funds in matters of preserving local culture. Data in this study were collected through observation, interview, and documentation techniques involving the Tegal Kenongo Village community. The results of this study indicate that special funds play a significant role in providing support for cultural activities, such as the implementation and preservation of traditional karawitan arts, gejog lesung, and increasing public awareness of the importance of maintaining ancestral cultural heritage. With the openness of the community in the use of special funds and periodic evaluations, the use of special funds is certainly expected to be more optimal in achieving the goals and expectations of the community, especially in maintaining the existence of local karawitan and gejog lesung arts.